A Risk Management Approach to Climate Adaptation in China - Sall, Chris (World Bank, Washington, DC, 2014)
This discussion paper provides the analytical backdrop for a series of papers on managing climate- and weather-related risks in China. It reviews and synthesizes the growing literature on risk-based management approaches to climate change adaptation and offers guidance on a process for decision making. Managing risks from severe weather, present-day climate variability, and future climate change is integral to China's development. While the effects of future climate change are deeply uncertain, this uncertainty should not preclude action. Risk management is in essence a process for designing, implementing, and evaluating policies in the face of such uncertainty. The paper begins by defining key concepts and establishes the context for climate risk management and adaptation in China. It then outlines a step-by-step process for a risk centered approach to adaptation. The focus of the process is on planning for adaptation, not policy implementation. The papers that follow in the series take the general framework set out by this paper and apply it to different sectors, including transportation, water utilities, urban planning, and forestry.